PROBLEM DAN SOLUSI ATAS PENERAPAN TA’ZIR DI PESANTREN (Studi Kasus di Pondok Pesantren Al Ibrohimy Galis Bangkalan) - Mo’tasim; Zaini Tamim AR (Universitas Islam Lamongan, 2020)
Initially, the application of ta'zir was considered normal among pesantren and the community. But lately, not a few who argue that ta'zir applied in pesantren is synonymous with violence. This study aims to analyze the problem of applying Ta'zir in Al Ibrohimy Galis Bangkalan Islamic boarding school along with alternative solutions that rely on Human Rights in Indonesia. The author uses descriptive qualitative research, with primary data sources Al Ibrohimy boarding school and board chair, as well as relevant secondary sources. Meanwhile, data collection techniques through observation, interviews, documentation and questionnaires. The findings of this study reveal that ta'zir in Al Ibrohimy Islamic boarding school is a way of disciplining troubled students to obey the rules of Islamic boarding schools. The application of ta'zir is also understood as a means of educating students to have a deterrent effect and not to repeat it. However, ta'zir sometimes makes students become depressed, traumatized and even physically and psychologically ill. Therefore, there must be aware of the pesantren that excessive ta'zir is an act that cannot be fully justified. Thus, all elements of pesantren must have ta'zir options that do not conflict with human rights. Besides, to minimize excessive ta'zir, a reconstruction of the system is needed that provides an alternative punishment for education. So that educational activities in boarding schools run dynamically and humanist